Neurocognitive and Adaptive Functioning in Young Patients with Severe Chronic Kidney Disease - Lijdsman, Sophie; Kerklaan, Jasmijn; Haverman, Lotte; Sandwijk, Marit S van; Bouts, Antonia H; Hoeck, Koen van; Jong, Huib de; Bemelman, Frederike J; Jaure, Allison; Groothoff, Jaap W; Oostrom, Kim J (Journal of Clinical Nephrology, 2024)
Background: To assess the association between neurocognitive functioning, adaptive functioning, and health-related quality of life (HRQoL), in Children and Young Adults with Severe Chronic Kidney Disease (CKD). Methods: We included patients with severe CKD (stages 4 and 5), aged 8-30 years, on different therapy modalities (pre-dialysis, dialysis, and transplanted) and healthy controls matched on age, sex, and parental education. All patients and healthy controls performed tasks to assess neurocognitive functioning (WISC/WAIS and a comprehensive neuropsychological test battery), and completed questionnaires to assess adaptive functioning (WFIRS or WHODAS) and HRQoL (PedsQL). Group differences were explored using MANCOVA. Mediation analyses were done to explore whether the relation between neurocognitive functioning and HRQoL was mediated by adaptive functioning. Results: 28 patients with severe CKD and 21 healthy matched controls were included. CKD patients had worse HRQoL (p < .001) than healthy controls. Adaptive functioning problems increased with age in the CKD patient group but not in the healthy control group (significant interaction effect: p = .024). Significant mediation effects were found, where impaired adaptive functioning mediated the relation between both low estimated Full Scale Intelligence Quotient (eFSIQ) and worse Processing Speed & Working Memory, and impaired HRQoL (eFSIQ: 95% confidence interval = .01-.58; Processing Speed & Working Memory: 95% confidence interval = 2.31-16.36). Conclusion: We found that impaired neurocognitive functioning is associated with worse HRQoL, which is conditional to impaired adaptive functioning. Especially towards young adulthood problems in adaptive functioning are more likely to be reported than when patients are younger.